Mapeamento sísmico da FM. Calumbi no campo de Carapitanga, bacia de Sergipe-Alagoas - Soares, Isabela Ramos (2019)
The Calumbi Formation, drifte section of the Sergipe-Alagoas Basin, although having an important role in the production of hydrocarbons, has its geology not discussed openly. The Carapitanga field is a marginal accumulation field located in the northern area of the basin and oil and gas producer in this Formation. The present work carried out the seismic analysis, applying the concepts of seismostratigraphic interpretation, such as terminations, external patterns and external architecture of reflectors, which allowed the recognition and mapping of sismofacies that, in turn, allowed inferring limiting surfaces, identifying transgressive and regressive events along the deposition of the Formation in the field area. This mapping also recognizes the presence of canyons of about 4km that reposition themselves along the geological time, suggesting a depositional model for this area of the Carapitanga field.